Study of the susceptibility to geological phenomena in linear works (Andalucía, Spain) - Pacífico Bedón, Tatiana (2012)
The present work has consisted of the study of the susceptibility of the land to slope movements by means of the use of Systems of Geographical Information (SIG) and its validation with techniques of field of a section of the Road of the Mediterranean situated on Albuñol’s municipality, Granada’s province, Independent Community of Andalucía, Spain. The SIG’s analysis was made with the software ArcGis 9.2 keeping in mind factors such as: topography, litology and geology of the zone. Of the results obtained is observed than 81% of the area of study presents low and very low susceptibility, the 14% a medium susceptibility degree and only the 1% to the 5% presents degree susceptibility high and very high. The works of field have permitted to contrast the information derived of the analysis SIG, with a very good level of correlation. The method presented is useful and fast, it owed to the automatic capture of most of the factors. Its main inconvenient is its dependence to a Digital Model of Elevations (MDE) of highly resolution.